Depression and its determinants in children and adolescents with obesity - Shin, Sabina (My University, 2015)
There is increasing recognition of the relationship between depression and obesity in the pediatric population and recently, there has been a focus on inflammation as a potential link. Both conditions are considered to be pro-inflammatory states, and certain inflammatory markers are linked to depression in obese adults and vice versa. Leptin has also been implicated in depression as a potential mediator between inflammation and depression. Brain derived neurotrophic factor (BDNF), which is associated with depression and obesity, is influenced by inflammation and leptin in animal models as well. Few studies have examined the interactions between depression, adiposity, and biological markers in obese youth and therefore, our objective was to explore the determinants of depression in obese youth in a clinical setting. We studied 244 youth aged 8-17 years (125 girls, 119 boys) at the time of entry to a weight management program, as part of a prospective, longitudinal study. The CES-DC depression-screening tool was used to assess depressive symptoms, and a participant was classified as having high depressive symptoms if the CES-DC score ≥15 or taking antidepressants. Questionnaires assessed socio-demographic factors and puberty while adiposity was measured using dual-energy X-ray absorptiometry (DXA). Inflammatory markers (IL-6, TNFα, CRP, IL-10), leptin, and BDNF were quantified by immunoassays. Of the 244 participants, 8 were on antidepressants and 88 (36.4%) met the criteria for high depressive symptoms. We confirmed previous findings that household income and body fat were important determinants of depressive symptoms. However for the first time, it was identified that leptin levels predicted CES-DC score independent of body fat. Neither inflammatory markers nor BDNF were significantly related to depression scores. Our findings suggest that leptin may mediate the relationship of adiposity and depression but it is uncertain if this is related to direct action or to the phenomenon of leptin resistance.
Depression and its determinants in youth with obesity
Keywords: Obesity; Pediatrics; Depression; Mental Health; children and adolescents; inflammation; BDNF; leptin; body fat; anthropometric; socio-demographic factors; HPA axis; clinical research